2021
DOI: 10.3389/fpls.2020.622213
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture and Genomic Prediction of Cooking Time in Common Bean (Phaseolus vulgaris L.)

Abstract: Cooking time of the common bean is an important trait for consumer preference, with implications for nutrition, health, and environment. For efficient germplasm improvement, breeders need more information on the genetics to identify fast cooking sources with good agronomic properties and molecular breeding tools. In this study, we investigated a broad genetic variation among tropical germplasm from both Andean and Mesoamerican genepools. Four populations were evaluated for cooking time (CKT), water absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 86 publications
5
36
0
Order By: Relevance
“…Optimum ratio of training to testing populations for achieving the highest repeatable predictive ability was 70:30% training:validation for most traits. This level is within the range of what has been found for other studies of genomic prediction in common bean (Keller et al, 2020;Diaz L. M. et al, 2021;Diaz S. et al, 2021;Shi et al, 2021). At 90% training population, the highest average predictabilities as measured by r were achieved, but standard deviations were much larger, leading to less certainty in whether a prediction was accurate.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Optimum ratio of training to testing populations for achieving the highest repeatable predictive ability was 70:30% training:validation for most traits. This level is within the range of what has been found for other studies of genomic prediction in common bean (Keller et al, 2020;Diaz L. M. et al, 2021;Diaz S. et al, 2021;Shi et al, 2021). At 90% training population, the highest average predictabilities as measured by r were achieved, but standard deviations were much larger, leading to less certainty in whether a prediction was accurate.…”
Section: Discussionsupporting
confidence: 86%
“…GS models generally use many markers distributed across the genome, and as a result, are more effective than traditional MAS in selection for traits with many genes with small effect. GS has been applied to common bean for root rot ( Diaz L. M. et al, 2021 ) as well as to agronomic traits ( Keller et al, 2020 ), cooking time ( Diaz S. et al, 2021 ), and nematode resistance ( Wen et al, 2019 ; Shi et al, 2021 ) to discover genotypes with the best breeding values for recombination schemes, but deployment in breeding programs is only beginning.…”
Section: Introductionmentioning
confidence: 99%
“…Past research investigations have explained the relationship between seed properties, variety type, seed storage conditions, and cooking time [54,55]. Table 1 presents the physical properties reported in AYB seeds.…”
Section: Structure Of African Yam Bean Seedsmentioning
confidence: 99%
“…In addition, several studies have shown that nutrients such as minerals and proteins are conserved when grains are cooked over a short period. In contrast grains requiring long cooking hours usually lose a significant amount of nutrients [55,86]. Cooking methods reported in AYB include boiling, steaming, roasting, and frying.…”
Section: Cooking Quality In African Yam Beanmentioning
confidence: 99%
“…Genomic information is an important breeding tool to improve selection accuracy and to accelerate genetic gain in beans (Delfini et al., 2021; Diaz et al., 2021; Keller et al., 2020). However, selection for desirable traits also results in erosion of genetic diversity (Esquinas‐Alcázar, 2005; Trucchi et al., 2021) and inefficient selection procedures in crop breeding may lead to premature plateauing of genetic gain (Cowling et al., 2017).…”
Section: Introductionmentioning
confidence: 99%